(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: Breastfeeding should start as soon as possible, breastfeeding practices can be influenced by many factors, one of which is socioeconomic and demographic factors such as education, knowledge, employment, and family welfare. Based on an initial survey conducted by researchers distributing google forms to 10 breastfeeding mothers, it was found that 3 mothers could not provide exclusive breastfeeding because the milk was not smooth, 2 of them could not provide exclusive breastfeeding because the mother worked while 5 mothers could provide exclusive breastfeeding until the baby was 6 months old. Objective: Knowing the factors that influence the success of exclusive breastfeeding in infants > 6 months at Bhayangkara Banjarmasin Hospital in 2023. Methods: The study used a cross sectional design. The population of this study were all mothers who gave birth from April to June at Bhayangkara Hospital and had babies older than 6 months. The sampling technique used purposive sampling with a total sample of 66 people and analysis using chi square. Results: The results showed that the significant value of age is p value 0.075 (>0.05), education p value 0.642 (>0.05), occupation p value 0.001 (<0.05), parity p value 0.054 (>0.05), pregnancy distance p value 0.431 (>0.05), occupation p value 0.001 (<0.05) which means it has a relationship with the success of exclusive breastfeeding. Conclusion: The results of this study indicate that the factors that influence the success of exclusive breastfeeding in infants > 6 months at Bhayangkara Hospital are work factors with the results of chi square analysis with a p-value of 0.001 (<0.05).